PERANCANGAN APARTEMEN DENGAN PENERAPAN ARSITEKTUR HIJAU DI CENGKARENG, JAKARTA BARAT - Rico Dwi Andrean; Inggit Musdinar Sayekti Sihing Yang Mawantu; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
This research focuses on designing apartments with the application of green architecture in Cengkareng, West Jakarta. Rapid population growth in the region has led to a scarcity of residential land and rising property prices. Data from the Central Statistics Agency (BPS) shows that the population of DKI Jakarta will increase to 10.64 million in 2022. A similar problem occurs in West Jakarta, especially in Cengkareng, which is a business center. Many workers have difficulty getting affordable housing near their workplace. The proposed solution is to build apartments with a green architectural approach. This apartment will be a solution for people who need housing near workplaces and public facilities, while reducing irregular development. Apart from being a residence, this apartment can be used as an investment or business opportunity through temporary leasing. The aim of this research is to design apartments that meet the needs of the people of West Jakarta, especially Cengkareng, by paying attention to aspects of green architecture. Another goal is to reduce the gap between housing and workplaces and provide adequate facilities. The approach to problem solving involves analyzing human, environmental and building aspects. Data collection was carried out through field surveys, comparative studies, observations, and literature studies. Primary and secondary data are used to design apartments as needed. Hopefully, this apartment can answer the problem of housing availability in West Jakarta while prioritizing sustainability.